Hvad taler vi om, når vi taler om Bernhard? - Nielsen, Nielsen; Frantzen, Mikkel Krause (Passage - Tidsskrift for litteratur og kritik, 2013)
Nielsen & Mikkel Krause Frantzen: “What do We Talk about When We Talk about Thomas Bernhard?” What do we talk about when we talk about Thomas Bernhard? What does Bernhard himself talk about when he talks? And goes on talking? To us and in us and far beyond us? What is it? What? Acting as the two cerebral hemispheres in a Bernhard caused concussion, Nielsen and Mikkel Krause Frantzen (each deeply lost in his own sphere and yet generating some sort of interference and reverberation between the two), try to recover by laying bare the sense of reading Bernhard: Why are we laughing, what exactly is it that makes us laugh, and what is it that finally, towards the End, always touches us, deeply, when we read and read and read Thomas Bernhard? This attempt leads through the canonized and dangerously infecting écriture-voice of Bernhard, through the self-creating self-destruction, the status of suicide and the absolute Truth, the excited misanthropy versus human compassion, the triangle of depression, melancholia & mania, the state of walking versus the state of getting nowhere at high speed, not to mention the scandal of the toilets in Austrian restaurants. And – of course – it all ends in the deadly Bernhardian laughter and Austria as the only qualified heavenly hell on earth.